Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee - Williams, James D.; Neely, David A.; Walsh, Stephen J.; Burkhead, Noel M. (Zootaxa, 2007)
Three new species of Percina are described from upland drainages of the Mobile Basin. Two of the three species are narrowly distributed: P. kusha, the Bridled Darter, is currently known only from the Conasauga River drainage in Georgia and Tennessee and Etowah River drainage in Georgia, both tributaries of the Coosa River, and P. sipsi, the Bankhead Darter, which is restricted to tributaries of Sipsey Fork of the Black Warrior River in northwestern Alabama. The third species, P. smithvanizi, the Muscadine Darter, occurs above the Fall Line in the Tallapoosa River drainage in eastern Alabama and western Georgia. In a molecular analysis using mitochondrial cytochrome b sequence data, P. kusha and P. smithvanizi were recovered as sister species, while Percina sipsi was recovered in a clade consisting of P. aurolineata (P. sciera + P. sipsi). Two of the three species, P. kusha and P. sipsi, are considered to be imperiled species and are in need of conservation actions to prevent their extinction. Description of these three darters increases the number of described species of Percina to 44. Sixteen are known to occur in the Mobile Basin, including nine that are endemic.